INFLUENCE OF THE DIGITAL ECONOMY ON ECONOMIC GROWTH IN INDONESIA - Ripira, Risti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Technological and digital developments that happening right now are rapidly growth and this condition encourages the competition in the business world become more intense. The rapid development of technology and digitalization has presented a digital business marked by the high development of technology-based business and trade transactions. Based on these, digital business has great potential to drive economic growth.Digitalization is an interesting topic to research in encouraging technological progress and stimulating economic growth. Economic activities nowadays cannot be separated from the use of information & communication technology through telecommunications networks and the use of internet by conducting e-business transactions. E-business or digital business is a projection of new talents that can inspire competitiveness. Digital business is currently growing rapidly around the world, including Indonesia, proven by the increasing number of internet users. The Indonesian Internet Service Providers Association (APJII) announced that the number of Indonesian internet users in 2024 reached 221,563,479 people from a total population of 278,696,200 people in Indonesia in 2023. This condition is also followed by the increasing number of e-commerce users in Indonesia which has continued to increase since 2020, until in 2023 the number of e-commerce users in Indonesia is 58.63 million users. The research method used is descriptive qualitative research, a method that been used by researchers through a literature study approach and analyzing all information regarding the research topic. This research intends to find out how does the impact of digital business on Indonesian economy. The results show that digitalization has changed many aspects of Indonesian society, including the economy. The development of technological advances and digitalization give  positive impact on Indonesia's economic growth.